Pengembangan Media Fun Thinkers Book Berbasis Scientific Materi Keragaman Budaya Indonesia Untuk Meningkatkan Self Regulation Pada Siswa Kelas IV UPT SDN Kebonduren 01 Kabupaten Blitar - Masyitho, Latifa Dewi; Mohamad Fatih; Cindya Alfi; Dewi Masyitho, Latifa; Fatih, Mohamad; Alfi, Cindya (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This study aims to produce development products in the form of teaching materials for class IV,namely the Scientific Based Fun Thinkers Book,material on Indonesia cultural diversity to improve student self regulation in this study using the development method (Research&Development) with the ADDIE development model ,Analysis (analysis), Design(design), Development(development), Implementation (Implementation) and Evaluation (evaluation).The data source in this study consisted of primary data obtained from the research environment,namely UPT SDN Kebonduren 01 Blitar Regency,with 18 class IV students as research subjects.the result showed that the development of scientific based fun thinkers book media on Indonesia cultural diversity material was carried out through the stages of observation,validation by media experts and material experts,linguists as well as field trials with fourth grade students at SDN kebonduren 01.The validity test was carried out by experts show valid result with percentages showing more than 91 %.while the increase in self regulation proved to increase by category with the result t count for self regulation of 8.5.